Diagnosis and treatment of spinal extradural arachnoid cysts: A chronic traumatic case report with review of the literature: Spinal extradural arachnoid cysts - Kullukçu , Hümeyra; Gürçay , Ahmet Gürhan; Kazancı , Atilla; Gürcan , Oktay; Özateş , Mehmet Özgür (Journal of Surgery and Medicine, 2023)
Arachnoid cysts are formed by duplication of the arachnoid membrane between the arachnoid and the pia mater. Although it is very common in intracranial localization, those with spinal location are rare. Extradural arachnoid cysts of the spinal canal are extremely rare pathologies regarded as either congenital or acquired. These cysts, which can develop idiopathic, post-traumatic, and after arachnoiditis, are often detected incidentally. They present with weakness in the extremities, neuropathic pain, paresthesia, or myelopathy. Here we describe the case of a 17-year-old male patient with a history of chronic spinal trauma who attended our clinic with severe low back pain for 7 months.